Artificial Intelligence in Education: Enhancing Usability and Adoption Among Educators in Digital Classrooms - Ms. Shivani Agrawal; Mr. Aakash Gautam (Recent Trends in Social Studies, 2026)
The use of Artificial Intelligence (AI) in education has changed digital learning environments. It provides new tools to improve teaching and boost student engagement. However, even with more AI-enabled technologies available, not all educators are using them equally. This uneven adoption is mainly due to problems with usability, accessibility, and digital readiness. This study addresses the critical gap between the potential of AI in education and its practical utilization by educators in digital classrooms.The primary objective of this research is to examine the factors influencing the usability and adoption of AI tools among educators and to explore strategies for enhancing their effective integration into teaching practices. The study uses a descriptive and exploratory research design. It relies on secondary data gathered from academic journals, industry reports, and policy documents. A thematic analysis method is used to find key patterns related to AI usability, educator acceptance, and barriers to implementation.The findings show that AI technologies like intelligent tutoring systems, automated assessment tools, and virtual assistants can greatly improve instructional efficiency. However, their adoption is blocked by issues such as technical complexity, lack of training, data privacy concerns, and limited support from institutions. The study further highlights that user-friendly design, professional development initiatives, and policy-level interventions play a crucial role in enhancing AI adoption among educators.This research contributes to the existing literature by emphasizing a human-centric approach to AI integration in education, focusing on simplifying technology to align with educators’ needs and capabilities. The study offers actionable insights for policymakers, educational institutions, and technology developers to create AI systems that are inclusive and accessible. Ultimately, fostering usability and trust in AI can accelerate its adoption, enabling educators to fully leverage its potential in creating effective and engaging digital learning environments.
Keywords: AI Adoption; AI Systems; Artificial Intelligence (AI) in Education; Digital Classrooms; Educational technology (EdTech); Usability of AI Systems